EpiPen STAT: A quality improvement project for anaphylaxis management. Issue 28 (1st October 2022) - Sato-DiLorenzo, Aya; Sendrowski, Brendan; Vasquez, Lora; Lithotomos, Rena; Olezkiewicz, Katarina; Shea, Meghan
Abstract : 319 Background: The medical oncology infusion unit at Beth Israel Deaconess Medical Center (BIDMC) experienced six anaphylactic reactions to chemotherapy between June 2000 and April 2021. EpiPen was delayed in all cases. In one instance, a patient experienced an emergency where she could not breathe, and her blood pressure continued to decrease. The covering nurse hesitated before administering an EpiPen. In follow-up, nurses reported a lack of confidence in administering an EpiPen. No licensed independent provider (LIP) was stationed in the infusion unit to guide nurses. The project's goal was to facilitate timely EpiPen administration, guided by the Translating Evidence into Practice (TRIP) framework. Methods: The project lead and the medical director revised the hospital's chemotherapy reaction guidelines to highlight anaphylaxis management. They established an interdisciplinary project team with medical, nursing, pharmacy, and informatics representatives. Interventions, which started in November 2021, included a reaction management algorithm and PRN-reaction orders allowing nurses to initiate interventions while waiting for a LIP arrival. The unit educator provided EpiPen training, and the pharmacy leaders created an adverse drug reactions (ADR) kit—a locked box with necessary medications that followed BIDMC's institutional algorithm to manage infusion reactions. Results: The project team collected post-intervention data between December 2021 and April 2022. Nurses reported twenty mild-to-severe chemotherapy reactions, including four anaphylactic episodes. Nineteen patients were discharged home on the day of reactions, and one patient required hospital admission for persistent symptoms. The management algorithm was followed in ten reactions (50%). Deviations from the algorithm were noted in eight cases, with the most frequent reason being smaller doses of antihistamine or corticosteroid. The algorithm was not applicable in two cases with atypical patient symptoms. In seventeen of the twenty reactions (85%), PRN-reaction orders were available in the electronic ordering system. The ADR kit was used in all reactions. In two of the four anaphylactic reactions, EpiPen was administered immediately following hypotension or hypoxia. In the remaining two cases, it was administered for persistent symptoms. Conclusions: The project facilitated EpiPen administration. The critical steps were systemic analysis of barriers, problem-solving with the TRIP framework, and engagement of frontline nurses. In our next step, we will consider narrowing the scope to managing acute hypotension or hypoxia. The narrower scope will enable targeted education about emergency management, potentially at the hospital's simulation center. To ensure every patient has an order, the department could consider a standing EpiPen order for hemodynamically unstable patients.